A description of vacancy complexes in an FCC solid solution within the framework of the CALPHAD Method. (December 2018) - Abe, Taichi; Shimono, Masato; Hashimoto, Kiyoshi; Kocer, Cenk
Abstract: Thermal vacancies and vacancy complexes in solids have not been treated explicitly in the CALPHAD-type thermodynamic assessments. Since thermal vacancies have important roles in phase transformations, precipitations and diffusion processes, it is necessary to describe them in the thermodynamic models for various simulations e.g. phase field simulations. In the present work, a description of the monovacancy for pure metals was expanded to vacancy complexes in an FCC solid solution in alloys where the interaction energies between vacancy-vacancy and vacancy-solute were taken into account using the Gibbs energy functions.